Bacteriological finding in the urethra in men with and without non-gonococcal urethritis - Tiodorović Jelica; Ranđelović Gordana; Kocić Biljana; Tiodorović-Živković Danica (Vojnosanitetski Pregled)
Background/Aim. Non-gonococcal urethritis (NGU) is a very common sexually transmitted disease. The etiology of the disease is complex and not completely solved. The aim of this study was to determine the bacteriological finding in the urethra in men with and without non-gonococcal utethritis. Methods. The study group comprised 200 men with symptoms of urethritis. The control group consisted of 60 men without symptoms of urethritis. The diagnosis of nongonococcal infection was made by finding of an increased number of polymorphonuclear leukocytes (≥ 5) under the microscope in a sample of Gram-stain of urethral smear (× 1 000) and without evidence of Neisseria. gonorrhoeae in specimens (negative direct microscopy and cell culture). Bacteriological examination included: direct microscopy with the Gramstained and methylblue-stained smears of urethral discharges, and cultivation of specimens under the aerobic/unaerobic conditions. In addition to standard bacterial examination and performinig direct imunofluorescence test to detect Chlamydia trachomatis (bioMerieux, France), urethral smears were also examined for the presence of Ureaplasma urealyticum and Mycoplasma hominis by commercially available Mycofast Evolution 2 test (International Microbio, France). The finding of mycoplasmas ≥ 104 CCU/ml was positive. The data were statistically analyzed using Pearson χ2 and Student t test. Results. C. trachomatis was predominant bacterial species found in urethra in men with nongonococcal urethritis. It was isolated alone and/or mixed with mycoplasmas and/or other bacteria in 86 (43.0%) of examinees. There was statistically significant difference in finding of C. trachomatis between the study group and the control group (p < 0.001). U. urealyticum was found in men with NGU: 30.2% were with C. trachomatis and 36.0% were without C. trachomatis (p > 0.05). In 16 (8.0%) men with NGU, C. trachomatis was isolated alone, while in 13.0% examinees it occurred with U. urealyticum. Staphylococcus saprophyticus was isolated in one subject with NGU, alone. Streptococcus agalactiae was found in 1.5% of men with urethritis. Anaerobic bacteria were found in 38 (19.0%) subjects with NGU and in 7 (11.7%) subjects from the control group. Conclusion. C. trachomatis was predominant bacterial species found in urethra in men with nongonococcal urthretitis. Mixed infections were frequent.